2006
DOI: 10.1159/000092466
|View full text |Cite
|
Sign up to set email alerts
|

Successful in utero Treatment of Fetal Goitrous Hypothyroidism: Case Report and Review of the Literature

Abstract: In this report, we present a case of fetal goiter with overdistended fetal neck and mild polyhydramnios. Amniocentesis and cordocentesis were conducted at 32 weeks’ gestation and fetal goitrous hypothyroidism was diagnosed. Intra-amniotic injection of l-thyroxine (T4) was performed with a weekly dose of 150 µg four times between 33 and 36 weeks’ gestation. In response to this in utero treatment, the goiter was reduced and polyhydramnios was improved. The mother gave birth to a healthy live male infant with nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…In reviewing the literature of the last 10 years, we found only 12 case reports of fetal goiter because of hypothyroidism treated in-utero [5][6][7][8][9][10][11][12][13][14][15][16] (excluding maternal Graves disease). However, information on the most relevant indices of an expanding goiter, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reviewing the literature of the last 10 years, we found only 12 case reports of fetal goiter because of hypothyroidism treated in-utero [5][6][7][8][9][10][11][12][13][14][15][16] (excluding maternal Graves disease). However, information on the most relevant indices of an expanding goiter, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The hormonal status can be confirmed with fetal blood sampling via cordocentesis or less invasively by amniocentesis. Although several reports of successful treatment have been published in recent years, the criteria for intervention are not always clearly defined given the risks involved [5][6][7][8][9][10][11][12][13][14][15][16]. From our perusal of the literature, it is clear that the main objectives of in-utero intervention are relief of polyhydramnios and of compression of the trachea because of a large goiter and hyperextension of the neck.…”
Section: Introductionmentioning
confidence: 99%
“…Since then a number of intra-amniotic levothyroxine injections have been performed. 110,111 A large meta-analysis has shown that the risk of abortion after mid trimester amniocentesis is quite small, which suggests that intra-amniotic levo thyroxine injections would also have a low risk of abortion. 102 Most cases of intra-amniotic levothyroxine injections have been without adverse events, however, there has been one reported case of preterm labor within 24 h of receiving the injection.…”
Section: Intra-amniotic Levothyroxine Injectionmentioning
confidence: 99%
“…Each included an intra-amniotic injection of levothyroxine at an initially calculated dose of 10 µg/kg of estimated fetal weight per day (increased to 20 µg/kg after 4 doses to achieve normal TSH levels). 4 …”
Section: Clinical Proceduresmentioning
confidence: 99%